A study of dysnatremia in patients admitted in medical intensive care unit of a tertiary care teaching hospital - Patel, Mantavya; Paliwal, Sanjay Kumar; Javed, Syed (International Journal of Advances in Medicine, 2021)
Background: Both dysnatremia at admission and that acquired in the intensive care unit (ICU) have been shown to have a direct influence on prognosis. The present was planned to study dysnatremia in adult patients admitting in medical intensive care unit (MICU). Methods: The present prospective observational study was conducted on patients admitted in medical ICU over a period of 1 year who developed dysnatremia during ICU stay. Patient’s age, sex, diagnosis at the time of diagnosis, comorbidities, serum sodium levels, risk factors, length of ICU stay, and survival status were noted. Results: Out of total 798 patients during the study period; 207 (25.94%) were found to have hypernatremia and 87 (10.9%) were hyponatremic. In hypernatremic group male/ female ratio was 125/82 and it was 50/37 in hyponatremic group. The mean ICU stay was significantly more in hypernatremic patients (4.76±3.57) compared to hyponatremic group (4.06±2.80). (p˂0.05) Mortality in both hypernatremic patients and hyponatremic patients was found significantly more in hypervolemic group which was 84.38% and 53.84% respectively. (p˂0.05) Conclusions: This study concluded that nowadays hypernatremia is more common with longer ICU stay. In both hypernatremia and hyponatremia mortality was found similar without any significant difference.